The Sufistic Dimension in Habib Luthfi Bin Yahya’s Syafahī Interpretation of Qur’anic Verses on Nationalism (International Journal of Education and Literature, 2025)
This study examines the Sufistic dimension in the syafahî interpretation of Habib Muhammad Luthfi bin Yahya regarding the verses of nationality in the Qur’an. Habib Luthfi was chosen as the object because he is a Sufi scholar as well as a national figure who consistently conveys Qur’anic interpretation through oral media, and his ideas demonstrate a combination of Sufi spirituality and nationalism. This study employs a qualitative method with primary data sources in the form of recorded lectures, religious gatherings, and direct interviews, as well as secondary data consisting of scientific literature related to tafsir, Sufism, and nationality. The analysis is carried out through a descriptive-analytical-comparative approach by paying attention to the methodology of tafsir and its Sufistic context. The results of the study indicate that the syafahî interpretation of Habib Luthfi is characterized as Sufistic-thematic with an approach of tafsir bi al-isyâri and bi al-ra’yi al-maqbûl which still rests on the framework of tafsir bi al-ma’tsûr. His interpretation of six verses of nationality emphasizes the value of love for the homeland, obedience to leaders, jihad in social-moral dimensions, the unity of the ummah, collective gratitude in national development, and respect for diversity as part of sunnatullah. Thus, this study affirms that Sufism can function as an ethical foundation of nationality as well as a model of Qur’anic interpretation that is relevant to contemporary Indonesian reality.